Environmental Parameters Affecting the Concentration of Iodine in New Zealand Pasture. Issue 5 (21st August 2019) - Jensen, Hayley; Orth, Barbara; Reiser, Rene; Bürge, Diane; Lehto, Niklas J.; Almond, Peter; Gaw, Sally; Thomson, Barbara; Lilburne, Linda; Robinson, Brett
Abstract : Iodine (I) is an essential trace element commonly deficient in agricultural systems. Whereas there is much information on I in food crops, there is a lacuna of knowledge on the environmental factors that affect pasture I concentrations. We aimed to identify the most important environmental factors affecting the concentration of I in New Zealand pastures, and the consequences to agricultural systems. Soil and pastoral samples were collected throughout the country and analyzed for I and other elements. The soils contained 1.1 to 86 mg I kg −1, with 0.005 to 1.4 mg kg −1 in the pasture. In 26% of pastures, I concentrations were insufficient for sheep nutrition, whereas 87% contained insufficient I for cattle nutrition. Pasture I concentrations were negatively correlated with the distance from the sea, and the concentration of oxalate‐extractable amorphous Al, Fe, and Si oxides, which immobilize soil I. Soil organic C and clay increased I retention in soil but did not significantly affect pasture I concentrations. Future work should investigate how soil properties affect pasture I uptake in inland areas. Core Ideas: 87% of New Zealand pastures contained insufficient iodine for cattle. Pasture I levels are higher close to the sea. Pasture I levels are lower in soil that is high in Fe and Al (oxyhydr)oxides.